Ascl1 coordinately regulates gene expression and the chromatin landscape during neurogenesis - Raposo, Alexandre A. S. F.; Vasconcelos, Francisca F.; Drechsel, Daniela; Marie, Corentine; Johnston, Caroline; Dolle, Dirk; Bithell, Angela; Gillotin, Sébastien; Berg, Debbie L. C. van den; Ettwiller, Laurence; Flicek, Paul; Crawford, Gregory E.; et al. (Cell reports, 2015)
The proneural transcription factor Ascl1 coordinates gene expression in both proliferating and differentiating progenitors along the neuronal lineage. Here, we used a cellular model of neurogenesis to investigate how Ascl1 interacts with the chromatin landscape to regulate gene expression when promoting neuronal differentiation. We find that Ascl1 binding occurs mostly at distal enhancers and is associated with activation of gene transcription. Surprisingly, the accessibility of Ascl1 to its binding sites in neural stem/progenitor cells remains largely unchanged throughout their differentiation, as Ascl1 targets regions of both readily accessible and closed chromatin in proliferating cells. Moreover, binding of Ascl1 often precedes an increase in chromatin accessibility and the appearance of new regions of open chromatin, associated with de novo gene expression during differentiation. Our results reveal a function of Ascl1 in promoting chromatin accessibility during neurogenesis, linking the chromatin landscape at Ascl1 target regions with the temporal progression of its transcriptional program.